La correcta identificación del daño sanitario como premisa para obtener su reparación: viejos paradigmas, nuevas soluciones - MARÍA JESÚS GALLARDO CASTILLO (Revista Vasca de Administración Pública)
There are two basic requirements that underpin any claim for damages and that condition a favourable response to the claim for compensation: the existence of the damage itself and its correct identification, which is not always a simple task since the legislation does not offer guidelines in this respect and the case law does so in a disparate manner and not always with uniform criteria. This task of identifying the damage is particularly complex in cases of omission of informed consent, in wrongful actions, in the doctrine of loss of opportunity and in disproportionate damage. This work will attempt to locate and provide answers and solutions to the many difficulties that arise in these cases and thus facilitate the articulation of claims in this area, which often see their claims for compensation rejected due to the complexity in the understanding and practical application of these figure.